Ruodlieb The Earliest Courtly Novel (after 1050) - Zeydel, Edwin H. (UNC Studies in the Germanic Languages and Literatures, 1959)
Considered the earliest courtly romance in Germany, "Ruodlieb" is an invaluable document of eleventh century European society and a fascinating link in the development of the novel of chivalry. This edition by Edwin H. Zeydel (first published in 1959) with Latin text and the first English translation on facing pages is based upon painstaking study of the manuscripts, with many fragmentary lines completed and 450 corrections of Langosch's text. Zeydel's introduction to the history of the text and appendices with literary commentary and textual notes make this the first critical edition of "Ruodlieb" utilizing the manuscript to appear since Seiler's work in 1882.